2005
DOI: 10.1002/jbm.a.30353
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation of injection molded PLA and self‐reinforced composite PLA after in vitro conditioning for three months

Abstract: Poly(lactic acid) (PLA) is used for medical devices such as sutures or orthopedic screws. A standard way to determine the loss of mechanical properties of a degradable polymer would be to soak the polymer in phosphate buffered saline (PBS) and test the desired property as a function of immersion time. This method is not sensitive enough to discern changes in mechanical properties through the cross-section of the polymer and neglects the degradation that is occurring at the molecular level. This article present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 25 publications
7
19
1
Order By: Relevance
“…The measured hardness of the PLLA film is 0.05 AE 0.01 GPa. The modulus and hardness of our PLLA thin films were lower than those previously reported for PLLA samples produced by injection molding (Young's modulus 4.6 GPa and hardness 0.23 GPa) [29]. This may be explained by different crystallinity of our PLLA samples produced by solution casting (more amorphous PLLA) and those reported in literature, which were subjected to elevated temperature and mechanical drawing during the injection molding process (more crystalline PLLA).…”
Section: Resultscontrasting
confidence: 73%
“…The measured hardness of the PLLA film is 0.05 AE 0.01 GPa. The modulus and hardness of our PLLA thin films were lower than those previously reported for PLLA samples produced by injection molding (Young's modulus 4.6 GPa and hardness 0.23 GPa) [29]. This may be explained by different crystallinity of our PLLA samples produced by solution casting (more amorphous PLLA) and those reported in literature, which were subjected to elevated temperature and mechanical drawing during the injection molding process (more crystalline PLLA).…”
Section: Resultscontrasting
confidence: 73%
“…Good agreement is found with literature values, in particular with the results obtained by Wright-Charlesworth et al 42 and Pillin et al 43 (4360 compared with 4600 and 4490 MPa for neat PLA modulus). However, these values obtained by nanoindentation present an overestimation of 20% compared with modulus measured by tensile test on normalized specimens (4360 compared with 3400 MPa for neat PLA modulus).…”
Section: Nanoindentation Measurements With Berkovitch Indentersupporting
confidence: 86%
“…Various techniques such as hot compaction [7], partial dissolution [8], cool drawing [9] and chemical modification [10] have been employed to manufacture self--reinforced composites. Several studies have reported on the successful production of SRCs using a wide variety of polymer fibres, including polyethylene (PE) [11--14], polypropylene (PP) [15,16], polyethylene terephthalate (PET) [17], polyamides [18,19], polylactic acid (PLA) [4,20,21], polyglycolic acid (PGA) [22,23] and polymethylmethacryalate (PMMA) [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li and Yao [33] produced 0.5 mm thick single PLA composites using amorphous PLA sheets (5% crystallinity) and crystalline PLA yarn (40% crystallinity) via a compression moulding process at 140 o C, and reported that the self--reinforced PLA composite containing 25 wt% unidirectional PLA yarns (consisting of 135 continuous fibres with average diameter of around 20 µm) had improved the tensile strength by 31% and modulus by 48% when compared to the control PLA sheet (tensile strength~44.8 MPa and modulus~2.5 GPa). The flexural properties of a 3.2 mm thick self--reinforced PLLA composite produced via a hot compaction process at 95 o C were investigated by Wright--Charlesworth et al [20] and reported that SR--PLLA had higher initial flexural properties (strength~139.2 MPa and modulus~5.4 GPa) when compared to non--reinforced PLLA (strength~110.8MPa and modulus~3.9GPa).…”
Section: Introductionmentioning
confidence: 99%